Effect of consolidation on the flexural creep behaviour of all-polypropylene composite (eXPRESS Polymer Letters, 2010)
The long-term viscoelastic behaviour of self-reinforced polypropylene composites (SRPPC) was studied by short-term flexural creep tests at different temperatures. As reinforcement a fabric, woven from highly stretched split PP yarns, whereas as matrix materials α and β crystal forms of isotactic PP homopolymer and random copolymer (with ethylene) were selected and used. The composite sheets were produced by film-stacking method and compression moulded at different processing temperatures (5, 20, 35°C above the melting temperatures of the matrices) keeping the holding time and pressure constant. The manufactured specimens were subjected to isothermal creep tests at different temperatures ranging from –20 to 80°C under an applied load. The time-temperature superposition principle was verified for the creep data. An Arrhenius type relationship described the shift data obtained from the creep tests. It was found, that with improving consolidation (increasing processing temperature) the creep compliance decreased and good correlation was found between creep compliance and density/peel strength.